THE MEDIATING ROLE OF BURNOUT IN THE RELATIONSHIP BETWEEN COMPENSATION AND SERVICE QUALITY AT KABUH COMMUNITY HEALTH CENTER - Nisfu Laily Shofiatujidda; Wisnu Mahendri; Emmanuel E. Uye (PT. Cadas Insan Madani, 2026)
This study examines the effect of compensation on service quality at Puskesmas Kabuh, Jombang, by testing burnout as a mediating variable. Using a quantitative explanatory research design with cross-sectional approach, the sample comprised permanent and contract employees selected through purposive sampling. Data were collected using Likert scale questionnaires and analyzed using PLS-SEM. The findings revealed that compensation has a significant positive effect on burnout, yet the direct effect of compensation on service quality is not significant. Conversely, burnout has a significant positive effect on service quality. Burnout fully mediates the effect of compensation on service quality with a significant mediation effect. The research model explains a substantial proportion of service quality variation. These findings suggest that service quality at Puskesmas Kabuh is currently maintained through unsustainable psychological sacrifice of employees, necessitating management to develop workload management and psychological support programs alongside compensation improvements.